Individual participant data meta‐analysis of the impact of educational interventions on pupils eligible for Free School Meals. (10th July 2021) - Ashraf, Bilal; Singh, Akansha; Uwimpuhwe, Germaine; Higgins, Steven; Kasim, Adetayo
Abstract : Meta‐analysis is the synthesis of findings from research projects, which enables an estimate of the average or pooled effect across various studies. This study presents findings from the intention to treat analysis for a series of educational evaluations in England using a two‐stage meta‐analysis with standardised outcome data and individual participant data meta‐analyses. The research estimates the overall impact of educational trials on pupils eligible for Free School Meals (FSM) and the attainment gap in literacy and mathematics performance between FSM and non‐FSM pupils based on analysis of 88 trials and data from over half a million pupils. For the meta‐analyses, frequentist and Bayesian multilevel models were used to estimate the individual and pooled effect size across categories of explanatory variables such as age groups (key stages in England) and aspects of the type of interventions (one‐to‐one, small group, whole class). Results indicated that the overall impact of interventions on the literacy outcomes of FSM pupils was positive, with a pooled effect size of 0.06 (0.03, 0.08). However, for mathematics, no overall effect on FSM pupils was observed. Analysis of the attainment gap indicated that literacy outcomes for FSM pupils were improved by interventions marginally more than for non‐FSM pupils (pooled attainment gap 0.01 (−0.01, 0.04)). The risk of bias assessment showed that estimates were consistent across different methodological approaches. Overall, evidence from this study can be used to identify, test and scale educational interventions in schools to improve educational outcomes for disadvantaged pupils.